From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (Global Arbitration Review, 2024)

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (10th Kuwait International Law School annual international academic conference (KILAW 2024), 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring,  as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document.  The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality